2022
DOI: 10.5325/transportationj.61.3.0231
|View full text |Cite
|
Sign up to set email alerts
|

Expectations vs Experience: Managing the Adverse Effects of Service Failures on Customer Satisfaction in the Airline Industry

Abstract: Airlines constantly seek to attenuate the negative impacts of operational service failures, namely arrival delays, mishandled baggage, and involuntary denied boarding, on customer satisfaction. Our study examines the roles of two management decisions—advertising expenses and flight personnel salaries—in shaping customer satisfaction via ex-ante expectations and the actual service experience, respectively. Drawing from expectancy disconfirmation theory (EDT) and the airline service quality literature, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…In addition, they show the most important aspects of services identified by the passengers assigned to each cluster group rating of Iberia, and the main aspects is about (1) quality of customer service which refers to the important of the performance of this service, (2) inflight experience, (3) punctuality of flight, (4) flight delays, ( 5) check-in, (6) personnel service. Research from Masorgo et al [102] using expectancy disconfirmation theory EDT, they found that both arrival delays and involuntary denied boarding negatively affect customer satisfaction, their results show the importance of managing passenger expectation about airline service and the inflight experience.…”
Section: Discussion Of Resultsmentioning
confidence: 97%
“…In addition, they show the most important aspects of services identified by the passengers assigned to each cluster group rating of Iberia, and the main aspects is about (1) quality of customer service which refers to the important of the performance of this service, (2) inflight experience, (3) punctuality of flight, (4) flight delays, ( 5) check-in, (6) personnel service. Research from Masorgo et al [102] using expectancy disconfirmation theory EDT, they found that both arrival delays and involuntary denied boarding negatively affect customer satisfaction, their results show the importance of managing passenger expectation about airline service and the inflight experience.…”
Section: Discussion Of Resultsmentioning
confidence: 97%
“…H2 reveals an inverse association between negative experiences and consumer expectations. Those who see service failures tend to lower their expectations (Hess, 2008; Masorgo et al. , 2022).…”
Section: Resultsmentioning
confidence: 99%